Linear, planar, and tubular molecular structures constructed by double planar tetracoordinate carbon D2h C2(BeH)4 species via hydrogen‐bridged BeH2Be bonds. Issue 2 (22nd July 2015) - Zhao, Xue‐Feng; Li, Haixia; Yuan, Cai‐Xia; Li, Yan‐Qin; Wu, Yan‐Bo; Wang, Zhi‐Xiang
Abstract : This computational study identifies the rhombic D 2 h C2 (BeH)4 (2a ) to be a species featuring double planar tetracoordinate carbons (ptCs). Aromaticity and the peripheral BeBeBeBe bonding around CC core contribute to the stabilization of the ptC structure. Although the ptC structure is not a global minimum, its high kinetic stability and its distinct feature of having a bonded C2 core from having two separated carbon atoms in the global minimum and other low‐lying minima could make the ptC structure to be preferred if the carbon source is dominated by C2 species. The electron deficiency of the BeH group allows the ptC species to serve as building blocks to construct large/nanostructures, such as linear chains, planar sheets, and tubes, via intermolecular hydrogen‐bridged bonds (HBBs). Formation of one HBB bond releases more than 30.0 kcal/mol of energy, implying the highly exothermic formation processes and the possibility to synthesize these nano‐size structures. © 2015 Wiley Periodicals, Inc. Abstract : D 2 h C2 (BeH)4 has been computationally characterized to be a species featuring double planar tetracoordinate carbons. Because of the electron deficiency nature of the BeH bonds, the species can serves as building blocks to construct nano‐size structures via the intermolecular hydrogen‐bridged ‐BeH2 Be‐ bonds (HBB), as exemplified by our reported molecular chains, planar sheets, and tubes. Formation of a HBB is exothermic by more than 30.0 kcal/mol, implying a possibility to synthesize these nano‐size molecules.